2016
DOI: 10.1177/096739111602400606
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties Study of E-Glass/Epoxy Laminate and π/4 Quasi-Isotropic E-Glass/Epoxy Laminate

Abstract: The usage of composites has increased in various fields, including automotive and aerospace, due to their high strength-to-weight ratio. The optimum use of composite material is also being studied to bring down the fuel costs and carbon emissions to atmosphere. The concept of optimum usage of composite material could be applied at the initial design stage or when repairing damaged composite structures. This paper describes preliminary work towards the optimum usage of π/4 quasi-isotropic E-glass/epoxy laminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…39,40 It has been known that the tensile strength in polymer composites highly dependent on the orientations of GFs. 41,42 The tensile strength of the GF reinforced polymer composites (without CNTs) for the combination of 0 and 90 fiber orientations and 60 wt% GFs was reported as about 400 MPa, [43][44][45] that is consistent with our data. The tensile tests for the composites with various MWCNT loadings were also performed as shown in Figure S1.…”
Section: Mechanical Propertiessupporting
confidence: 90%
“…39,40 It has been known that the tensile strength in polymer composites highly dependent on the orientations of GFs. 41,42 The tensile strength of the GF reinforced polymer composites (without CNTs) for the combination of 0 and 90 fiber orientations and 60 wt% GFs was reported as about 400 MPa, [43][44][45] that is consistent with our data. The tensile tests for the composites with various MWCNT loadings were also performed as shown in Figure S1.…”
Section: Mechanical Propertiessupporting
confidence: 90%
“…They showed that the tensile strength of 60 wt% of GF reinforcement was around 350–400 MPa, which is similar to our results with 55 wt% GF content. For unidirectional GF‐reinforced epoxy composites, the reported tensile strength reached 821 MPa with 0° fiber orientation and 27 MPa with 90° fiber orientation . The average tensile strength for the combination of 0° and 90° orientations of GFs in the composite was about 400 MPa.…”
Section: Resultsmentioning
confidence: 98%
“…However, the obtained longitudinal strength and stiffness of 1492 MPa and 123 GPa respectively measured here were higher than the 1400 MPa and 119 GPa listed by the manufacturer, suggesting that despite slight distortions in the fibre alignment within the samples, a good manufacturing quality was achieved for the samples, despite a slightly lower FVF (51.1% vs. 55% in the data sheet). Although it is difficult to find mechanical properties in literature for glass fibre reinforced epoxies with the same fibre architecture, the powder epoxy reinforced glass fibre composites performed well compared to conventional epoxy systems [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%